Pembelajaran Berbasis Sadar Bencana Bagi Guru IPS Tingkat SMP di Kota Semarang - Mulianingsih, Ferani; Suharini, Erni; Purnomo, Arif; Handoyo, Eko (Indo-MathEdu Intellectuals Journal, 2025)
This article examines efforts to enhance the capacity of junior high school social studies (IPS) teachers in Semarang City to integrate disaster awareness education into classroom instruction. The study employs a qualitative descriptive approach, conducted through a series of activities including training sessions, mentoring, and evaluations involving participating teachers. Data was collected through direct observation during training and mentoring, documentation of the teachers' lesson plan results, and in-depth interviews. Analysis was conducted using data reduction techniques, data presentation, and drawing conclusions. The findings indicate a significant improvement in teachers’ understanding of disaster concepts, risk mitigation, and the implementation of pedagogical strategies grounded in local wisdom. The program also successfully produced thematic learning modules that are practical and applicable for disaster-oriented social studies education. Overall, this article contributes to the advancement of disaster education integration within the junior secondary school curriculum.